Is web-based program effective on self-care behaviors and glycated hemoglobin in patients with type 2 diabetes: A randomized controlled trial - Maryam Eghtedari; Masoomeh Goodarzi-Khoigani; Maryam Sadat Shahshahani; Homamodin Javadzade; Parvaneh Abazari (Wolters Kluwer Medknow Publications, 2023)
Background: Diabetes Self-Management Education and Support (DSMES) as a framework focuses on seven self-care behaviors. Moreover, technology-assisted self-care education is increasingly suggested for patients with Type 2 Diabetes Mellitus (T2DM). Therefore, we examined the effect of a web-based program on self-care behaviors and glycated hemoglobin values in patients with diabetes mellitus. Materials and Methods: This randomized controlled clinical trial was conducted at Alzahra Hospital in Isfahan, Iran, between April and November 2020 and included 70 patients with T2DM. Data were collected using a questionnaire that included a demographic information section and a diabetes self-management section with 21 questions on a Likert scale. Fasting blood samples (2.50 ml) were collected before and after the interventions to measure HbA1c levels. The study intervention involved a web-based program that included multimedia educational content (such as videos, lectures, educational motion graphics, text files, posters, and podcasts) presented in seven sections based on DSMES over a 21-day period with monitoring by an instructor. Results: The mean scores for healthy eating (F = 3.48, p = 0.034) and medication adherence (F = 6.70, p < 0.001) significantly increased in the interventional group, while the mean scores for being active, monitoring, reducing risks, problem-solving, and healthy coping did not significantly change. Additionally, the mean differences in HbA1c values significantly improved in the interventional group compared to the control (F = 5,1, p = 0.026). Conclusions: A web-based program in accordance with DSMES improved HbA1c levels and increased scores for healthy eating and medication adherence in patients with T2DM. However, further research with larger sample sizes and qualitative interviews is needed.